Vertigo and dizziness, a global public health issue: Recommendations for an appropriate approach in Chile - Colipí Sáez, Jorge (2025)
Introduction: Vertigo and dizziness are common symptoms in clinical practice and have garnered increasing interest due to the significant costs they impose on healthcare systems worldwide. These symptoms have a substantial impact on individuals' functionality, increase the risk of falls, and are associated with various comorbidities. Proposal: This study provides information on the prevalence of vertigo and dizziness in Europe, the United States, and South America, and proposes a series of specific recommendations to address these issues within the context of Chile. Argumentation: Taking into account the Chilean healthcare model and the strategies of the primary care resolutivity program, practical suggestions are presented for healthcare professionals and family physicians. These recommendations incorporate the guidelines of the Bárány Society, as well as experiences and strategies developed in Europe and the United States. Conclusions: The proposals emphasize the importance of training primary care professionals in the use of the TiTrATE algorithm and the HINTS protocol, improving infrastructure and equipment for vestibular evaluation and rehabilitation, establishing a common language among clinicians, academics, and researchers regarding vestibular disorders, and developing a basic training plan in vestibular medicine.